Analisis Bibliometrik: Perkembangan Penelitian Mengenai Pelatihan Pegawai - Khamami Herusantoso; Yubilianto Yubilianto (Universitas Sains dan Teknologi Komputer, 2023)
Employee Training is an effort by companies or organizations or agencies to improve their performance through increasing employee productivity. As far as our research results are concerned, there is a lot of literature related to employee training, but there is no bibliometric analysis of research articles related to employee training. This research is aimed at analyzing classification, identifying trends, and analyzing opportunities for research topics related to employee training in the future. This research uses a combination of the Publish and Perish, Mendeley, and Vosviewer applications as well as a 5-stage methodology on the Scopus database. By using the keyword